An implicit iteration process for solving a fixed point problem of a finite family of multi-valued mappings in Banach spaces - Suantai S. (2014)
This work is concerned with the strong convergence of an approximating common fixed point sequence of a finite family of multi-valued mappings in a uniformly convex and smooth Banach space using an implicit iteration scheme introduced by Xu and Ori [H.K. Xu, R.G. Ori, An implicit iteration process for nonexpansive mappings, Numer. Funct. Anal. Optim. 22 (2001) 767-773]. © 2011 Elsevier Ltd. All rights reserved.